2022
DOI: 10.1093/geroni/igac059.1940
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health Underlie Racial/Ethnic Disparities in Psychological Health and Well-Being

Abstract: This study sought to determine the impact of selected social determinants of health on psychological health and well-being (defined as depression, cognition, self-rated health) among Black and Hispanic/Latinx adults relative to White adults aged 51 to 89. We measured disparities in depression, cognition, and self-rated health among 2,306 Non-Hispanic/Latinx Black, 1,593 Hispanic/Latinx, and 7,244 Non-Hispanic/Latinx White adults from the Health and Retirement Study (n=11,143). Blinder-Oaxaca decomposition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The beneficial effect of higher years of education on time to cognitive decline was different across racial and ethnic groups, such that White adults, on average, evidenced the longest benefit of 13 years, followed by Latinx adults with 12 years, and Black adults with 10 years. These findings were consistent after controlling for a variety of socioeconomic, medical, and psychosocial inequities 25,32 that are known to affect cognitive functioning among Black and Latinx adults in addition to selective attrition and decline due to all‐cause mortality.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The beneficial effect of higher years of education on time to cognitive decline was different across racial and ethnic groups, such that White adults, on average, evidenced the longest benefit of 13 years, followed by Latinx adults with 12 years, and Black adults with 10 years. These findings were consistent after controlling for a variety of socioeconomic, medical, and psychosocial inequities 25,32 that are known to affect cognitive functioning among Black and Latinx adults in addition to selective attrition and decline due to all‐cause mortality.…”
Section: Discussionsupporting
confidence: 58%
“…Though our study attempted to control for potential confounding factors such as socioeconomic status 32 and medical comorbidity, 39,40 it is conceivable that other contextual factors such as educational quality, 41 literacy rates, 41 perceived discrimination, 36,37 stereotype threat, 35 test bias, 38 and inequities in psychosocial health and social determinants of health 25,32,42 influenced participants' cognitive performance. While previous studies have found similar rates of cognitive decline among Black, Latinx, and White adults in the HRS, 24 our study found different rates of decline using non‐linear modeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet another examines the associations between social support from different types of relationships and psychological well-being, along with the mediating effects of satisfaction of basic psychological needs in these associations [47]. An attempt has even been made to determine the impact of specific social determinants of health on psychological health and well-being among older Black and Hispanic/Latino adults compared to White adults [48]. More focused on our educational context is research that evaluated the preliminary effects of a WeChat-based educational intervention on the social participation of older adults in China, finding significant improvements in social participation and self-worth [49].…”
Section: Discussionmentioning
confidence: 99%
“…Social determinants of health (SDoHs) are social and structural factors that affect incidence, prevalence, and course of diseases as well as health inequities and reportedly account for 30–55% of health outcomes, exceeding the contribution from medical factors (World Health Organization, 2008). SDoHs impact physical, mental, and cognitive function and longevity among all age groups including older adults (Jeste, 2022; Jester et al ., 2023). Over recent decades, the construct of social connections has acquired increasing attention as an SDoH.…”
Section: Introductionmentioning
confidence: 99%